Художественная культура в Украине: жизнь после смерти старого мифа - Шульга, Р. (Социология: теория, методы, маркетинг, 2001)
Realities of modern cultural life in Ukraine give the ground to state that the epoche when culture was considered a moral shepherd knowing the way of mankind salvation is over. New conditions have emerged both for cultural production and for communication with art. However the essence of changes is neither realized to full extent nor accepted by everyone as the actuality. The most of artists adhere still the mythologems of the past. The article analyses collisions, which determine current state of the modern Ukrainian culture.